Contemporary Israeli-Turkish relations in comparative perspective - Sever, Ayşegül (Palgrave Macmillan, 2019)
"This edited volume explores the Israeli-Turkish relations in the 2000s from a multi-dimensional perspective providing a comparative analysis on the subjects of politics, ideology, civil society, identity, energy, and economic relations. The contributors from both countries offer insights on the complex situation in the Middle East which is important for the understanding of the contemporary region. The work will appeal to a wide audience including academics, researchers, political analysts, and journalists" (Verlagsbeschreibung)